PUBLIC FINANCIAL MANAGEMENT PRACTICES IN INDONESIA LOCAL GOVERNMENT - A CASE IN MOJOKERTO REGENCY, EAST JAVA - Vadra, Karina Pearlaura; Amin, Fadillah; Sentanu, I Gede Eko Putra Sri (Erudio Journal of Educational Innovation, 2025)
This study explores the implementation of Public Financial Management (PFM) in Mojokerto Regency, East Java, with a specific focus on the consistency between planning and budgeting within the infrastructure, health, and education sectors. Using a qualitative approach, the study combines the PEFA framework assessment, NVivo-assisted text analysis, and semi-structured interviews with key local government stakeholders. Finding reveals that overall consistency level can be categorized as “C”, reflecting moderate misalignment between plans and budgets—particularly in the education and health sectors, while the public works sector demonstrates relatively stronger alignment. The analysis identifies three key themes which influencing consistency: institutional and regulatory frameworks, organizational capacity and responsiveness, and political and strategic influence. While digital tools like SIPD have improved procedural discipline, rigid regulations and limited adaptive capacity constrain responsiveness. Political dynamics, including legislative aspirations and executive interventions, further complicate budget alignment. This study recommends strengthening planning and budgeting framework by upgrading planning systems for real-time flexibility, enhancing organizational capacity through targeted training and rapid response mechanisms, and fostering early engagement of political actors to promote shared ownership and continuity. These measures aim to strengthen planning–budgeting integration and improve the effectiveness of local public financial management in decentralized settings.